2015
DOI: 10.1371/journal.pgen.1005420
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleosome Acidic Patch Regulates the H2B K123 Monoubiquitylation Cascade and Transcription Elongation in Saccharomyces cerevisiae

Abstract: Eukaryotes regulate gene expression and other nuclear processes through the posttranslational modification of histones. In S. cerevisiae, the mono-ubiquitylation of histone H2B on lysine 123 (H2B K123ub) affects nucleosome stability, broadly influences gene expression and other DNA-templated processes, and is a prerequisite for additional conserved histone modifications that are associated with active transcription, namely the methylation of lysine residues in H3. While the enzymes that promote these chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 81 publications
(108 reference statements)
4
45
0
Order By: Relevance
“…This result is also observed upon mutating H2A Glu93, a residue located toward the center of the NCP disk (Figs. 1C and 5D, lanes 2 and 6), and is consistent with a previous report (23). In marked contrast, H2A Glu57 and Glu65 mutations showed increased H2B Lys123∼Ub levels.…”
Section: Xl-ms Captures the Transient Bre1 Ring-rad6supporting
confidence: 91%
See 1 more Smart Citation
“…This result is also observed upon mutating H2A Glu93, a residue located toward the center of the NCP disk (Figs. 1C and 5D, lanes 2 and 6), and is consistent with a previous report (23). In marked contrast, H2A Glu57 and Glu65 mutations showed increased H2B Lys123∼Ub levels.…”
Section: Xl-ms Captures the Transient Bre1 Ring-rad6supporting
confidence: 91%
“…It was previously suggested that acidic histone residues are required to maintain normal cellular H2B∼Ub levels in Saccharomyces cerevisiae (22,23). However, it has remained unclear whether those residues mediate a direct physical interaction with Rad6-Bre1, or whether their mutation indirectly perturbs chromatin architecture or affects other transcription components.…”
mentioning
confidence: 99%
“…6A). No changes in histone H3K4 methylation levels were observed, which is in line with studies that show that reduced H2B-K123ub1 levels can occur without significant effects on H3K4 methylation (56). Taken together, these data show that CKII is an important regulator of histone H2B-K123ub1, likely through its regulation of PAF-C and FACT.…”
Section: S/t]xx[e/d] (47) Sdxe Sxx[e/d] and [D/e]s[d/e]x[d/e] And supporting
confidence: 89%
“…Another E3 ligase, RNF168, may not bind directly to the H2A/H2B acidic patch, but nonetheless requires an intact H2A/H2B acidic patch for nucleosome and H2A/H2B dimer ubiquitylation [33,34]. In S. cerevisiae , acidic patch mutations disrupt histone modification patterns including H2B K123 ubiquitylation and downstream H2A K4 and K79 methylation [54,55]. It remains to be determined whether arginine anchors are used by these histone modifying enzymes in establishing these marks.…”
Section: Arginine Anchormentioning
confidence: 99%